2007
DOI: 10.1002/jqs.1124
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene loess‐palaeosol sequences in the Vojvodina region, north Serbia

Abstract: Late Pleistocene loess-palaeosol sequences are widespread in the Vojvodina region, with thicknesses reaching a maximum of about 20 m. Our investigations include more than 40 of these loess sections. Geochronology of the last glacial loess-palaeosol sequences, based on luminescence dating and amino acid racemisation, provides correlations between Upper Pleistocene loess-palaeosol sediments in Vojvodina and comparable deposits at other European localities. Sedimentary logs of magnetic susceptibility, grain-size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
206
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 252 publications
(231 citation statements)
references
References 52 publications
21
206
0
4
Order By: Relevance
“…Thirty eight species (3 freshwater gastropods, 34 terrestrial gastropods, 1 bivalve) were identified from 6500 whole [9] and Stevens et al [27]; the datum 114 kyr is an unestimated age). (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty eight species (3 freshwater gastropods, 34 terrestrial gastropods, 1 bivalve) were identified from 6500 whole [9] and Stevens et al [27]; the datum 114 kyr is an unestimated age). (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…New results have been attained from paleoecological analyses of the southern part of the Carpathian Basin [1][2][3][4] especially in the field of Quaternary malacological analyses in the Vojvodnia (Vajdaság) region [5][6][7][8][9][10]. Malacological studies merit to Endre Krolopp, Quaternary malacologist (who passed away in 2010), and his follower Pál Sümegi and finally his Ph.D. students Dávid Molnár and Júlia Hupuczi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the paper of Jary and Ciszek (2013), the labelling system proposed by Kukla and An (1989), slightly modified by Markovic et al (2008) for Late Pleistocene litho-pedostratigraphic units in Voivodina is used.…”
Section: Study Area and The Geological Set-tingmentioning
confidence: 99%
“…This ob ser vation con tra dicts Ložek's views (1965) con cern ing the con sid erable ho mo ge ne ity of the loess fau nas of Eu rope. Loesses sit uated in an area south of the Carpathians and the Sudetes are usu ally char ac ter ized by a far more di ver si fied mol lus can fauna (Ložek, 1965(Ložek, , 1969(Ložek, , 1991(Ložek, , 2001Sümegi, 1995Sümegi, , 2005Krolopp and Sümegi, 1995;Sümegi and Krolopp, 2002;Markoviae et al, 2008). Par tic u larly sig nif i cant is the abun dance of the xerophilous spe cies, which man i fest at con sid er ably higher tem pera tures.…”
Section: Discussionmentioning
confidence: 99%